Uncertainty and self‐efficacy in parents of a child with congenital cataract-New implications for clinical practice - Jenny Gyllén; Gunilla Magnusson; Anna Forsberg (Wiley, 2019)
Abstract Aim The aim was an in‐depth exploration of uncertainty and self‐efficacy among parents of a child with congenital cataract by means of two theoretical frameworks to re‐design family care. Design A directed content analysis in accordance with Hsieh & Shannon, using Mishel's theory of uncertainty and Bandura's self‐efficacy theory. Methods Open‐ended, in‐depth interviews were conducted with 23 parents of a child with congenital cataract; six mothers, five fathers and six couples. Results In this novel study, self‐efficacy was interpreted as the ability to balance between uncertainty and acceptance. The performance accomplishment of the child and parents bridges the gap between uncertainty and acceptance by reducing uncertainty, thus constituting the level of self‐efficacy. Setbacks and complications increase uncertainty and reduce self‐efficacy, thus performance accomplishment is a mediator of self‐efficacy, while ability to master uncertainty determines the level of self‐efficacy.